Comparative visibility of planetary auroral radio emissions and implications for the search for exoplanets - Lamy, L.; Waters, J. E.; Louis, C. K. (My University, 2023)
The auroral regions of the so-called radio planets are the source of powerful, non-thermal, radio emissions amplified by an electron-wave resonant instability. These emissions are produced near the planetary magnetic poles along high latitude magnetic flux tubes at altitudes ranging from above the atmosphere up to a few planetary radii, and over variable ranges of local time and longitude. The radiated waves are also beamed at large angles from the local magnetic field vector, along a hollow cone, and further affected by refraction along the ray path. As a result, the final visibility of planetary auroral radio emissions strongly depends on the position of the observer. The underlying electron acceleration mechanisms depending on the considered magnetosphere, understanding the overall visibility of radiated waves is important to assess the diagnostic brought by remote radio observations onto auroral and magnetospheric dynamics. This topic has been widely studied in the literature, taking advantage of space-based radio exploration, generally on a planet-by-planet basis. In this work, we present an updated view of the visibility of Saturn's kilometric radiation from the full set of Cassini/RPWS observations obtained over 2004-2017. We then review comparatively recent parallel studies of the visibility of Terrestrial kilometric radiation and of Jovian broadband kilometric, hectometric and decametric emissions. We finally discuss the implications for the search for exoplanetary auroral radio emissions.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED